Peningkatan Kompetensi Mahasiswa Melalui Pelatihan Dasar Penggunaan ArcGIS untuk Pemetaan Geospasial - Arief Rachman B; Syaiful Ramadhan Harahap; Yusapri Andi; Nurhasan Nurhasan; Mohd Riza Fahlifi SF; Gunawan Syahrantau; Selvia Selvia; Ahmad Hafiz; Azmi Azmi; Sugianto Sugianto (CANANG: Jurnal Pengabdian Masyarakat, 2025)
This community service training program aims to enhance students' competencies in using Geographic Information System (GIS) software, specifically ArcGIS, for spatial data mapping and analysis. The significance of GIS in various fields, such as agriculture, environmental management, and urban planning, has grown, making it a valuable skill for students to acquire. The training was conducted in a hands-on format, combining theoretical lectures, practical exercises, and Focus Group Discussions (FGD) to promote active learning and collaboration. The participants, primarily students from the University of Islam Indragiri, were taught to collect geospatial data using Avenza Maps, process the data using ArcGIS, and create basic maps. The results showed a substantial improvement in the participants’ understanding and practical skills, with an average increase in comprehension of 42%. The program was highly appreciated by the participants, who found it beneficial for both their academic studies and future career prospects. In conclusion, the training successfully enhanced students' GIS proficiency, which is crucial for their academic development and employment opportunities, particularly in fields that require geospatial analysis and mapping skills.